“Tham Khwan Khwai – Kin Khao Mai – Sam Pasa Huajai Diawkan” in Ban Kwaw, Ban Namphu, Khiri Mat, Sukhothai - Wongsawad, Thutsapong (Journal of Cultural Approach, 2022)
The objectives of this study are 1) to investigate personal factors influencing participation and opinions of the “Tham Khwan Khwai – Kin Khao Mai – Sam Pasa Huajai Diawkan” ceremony traditional local for a good harvest and good fortune in Ban Kwaw, Ban Namphu, Khiri Mat, Sukhothai; 2) to study the differences of the personal factors and opinions of the ceremony; and 3) to discover the relationship between the opinions on the ceremony, lifestyles, beliefs, rites, and community relations. The sample group consisted of 361 people from Ban Namphu, Khiri Mat, Sukhothai and were selected via simple random sampling (number table). Interviews and questionnaire were employed as study tools, as well the statistics used for data analysis were mean and standard deviation. The statistics for the test are t-test and F-test by One-Way ANOVA and Pearson product moment correlation. The personal factors revealed that most of the questionnaire participants are female who are older than 50, have graduated with lower than a bachelor degree, earning less than 10,000 baht per month, and farm for a living. The analysis revealed that it is at a high level. The results of the gathered opinions indicate that the “Tham Khwan Khwai – Kin Khao Mai – Sam Pasa Huajai Diawkan” ceremony is significant for the community and it is empirically shown by the 0.05 statistical significant.